In vitro antioxidant activities of black cumin seeds oil and computational evaluation of thymoquinone and thymohydroquinone as inhibitors of EGFR tyrosine kinase - Mohammad, A.M.; Rimon, P.; Kashif, G.; Rukshana, A.H.; Tuhina, C.; Nurul, A.; Ferdosh, Sahena; Azad, A.K. Azad; Sarker, Md. Zaidul Islam (Elsevier, 2018)
The objective of the study is to assess and compare the total phenolic and flavonoids contents and antioxidant activities of black cumin (BC) seeds and oils (petroleum ether (PE) and n-hexene (HE) extracts and locally available BC oil), including the potential activity of thymoquinone (TQ) and thymohydroquinone (THQ), the two most significant lead molecules of BC seeds, against EGFR tyrosine kinase through molecular docking studies. Aqueous mixture of methanol, ethanol, and acetone at different concentrations of 50%, 70%, and 100% (pure) (v/v), respectively, including distilled water at the temperature of 100°C were used for the extraction of phenolic and flavonoid from the seeds and oils. Seeds were signified as high in phenolic in these analyses at the amount of 0.55 g TAE in 70% acetone extract that contained 0.950 g antioxidant capacities and inhibited 79.06% DPPH in the same solvent extract. In comparison of oils, elevated amount of phenolic was revealed in PE-extracted oil as 0.498 g TAE in pure ethanol extract and also found as high in inhibition of DPPH as 76.49%, although quantified as low in antioxidant capacities rather than BC oil of local market and HE extract. In flavonoid analysis, HE-extracted BC oil contained the most flavonoid contents in 70% acetone extract as 0.076 g rather than BC oil of local market and PE extracts and seeds, respectively. In search of the medicinal activity of TQ and THQ, the two most prominent compounds of BC seeds and oil, through in silico approach, TQ and THQ have successfully shown the inhibitory activity of EGFR (epidermal growth factor receptor) tyrosine kinase that is overexpressed in the development of tumor cell. Both of them interact with the common binding site residue of EGFR tyrosine kinase that is similar to the binding site of the FDA-approved drug Osimertinib. The binding affinity of TQ and THQ was found as − 7.592 and − 6.334 kcal/mol, respectively, and those are almost near to the binding affinity of Osimertinib as − 8.33 kcal/mol. For better understanding of molecular orbital reactivity and their thermodynamic properties of those leading compounds, the density functional theory was governed. The gap energy of TQ and THQ was found to be 0.14091 and 0.28485 eV, respectively.